Pengaruh Sikap dan Norma Subyektif Terhadap Niat Membeli Produk Barik di Kampung Batik Laweyan Surakarta - Hartati, Dhian Putri; Nurtantiono, Andri (Graduasi: Jurnal Bisnis & Ekonomi, 2015)
The  purpose  of  this  research  is:  1)  To  determine  the  effect  of simultaneously between  attitude  and  subjective  norm  on  the  intention  to  buy  the  product  as  namely Kampung  Batik  Laweyan  in  Surakarta,  2)  To  determine  the  effect  of  partially  between attitude  and  subjective  norm  on  the  intention  to  buy  the  product  as  namely Kampung Batik Laweyan in Surakarta. The  analyze  used  in  this  research  are:  Multiple  Regression  Analysis,  t  test,  F test, analysis Coefficient of Determination. Based on the analysis, it can be concluded: 1)  Attitudes  and  Subjective  Norms  have  significant effect  on  the  intention  to  buy  the product simultaneously as namely Kampung Batik Laweyan in Surakarta, 2) There is a partial effect between attitude and  subjective norm on the intention to buy the product as namely Kampung Batik Laweyan in Surakarta.  The advice  given  is:  1) The  advice  given is: 1) To  the enterprises as  namely  Kampung Batik Laweyan in Surakarta, cultivated more attention to consumer attitudes and subjective norms that influence  the intention to  buy batik clothes. 2) To other researchers, is  expected  to incorporate other  variables that  affect  the intention to  buy batik  products.2)  To  other  researchers,  is  expected  to  incorporate  other  variables  that affect the intention to buy batik products